2005
DOI: 10.1111/j.1365-2230.2005.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular 'nonscarring' mucous membrane pemphigoid associated with antilaminin-5 antibodies

Abstract: Mucous membrane pemphigoid is a rare, chronic autoimmune disease characterized by subepidermal blistering and scarring, predominantly affecting mucous membranes. Ocular involvement frequently occurs and often represents the only manifestation of the disease. We describe a 62-year-old woman with a bilateral 18-month duration of conjunctival hyperaemia, associated with erythema and oedema of the eyelids, lacking any typical ocular signs of mucous membrane pemphigoid such as sub-conjuctival fibrosis and scarring.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Our patient without mucosal involvement should be differentiated from IgA type anti-laminin-332 MMP, only 3 cases of which have been reported thus far (9)(10)(11). Two cases had severe mucous membrane involvement and were refractory to treatments (9, 10), while another case had only ocular lesion (11).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our patient without mucosal involvement should be differentiated from IgA type anti-laminin-332 MMP, only 3 cases of which have been reported thus far (9)(10)(11). Two cases had severe mucous membrane involvement and were refractory to treatments (9, 10), while another case had only ocular lesion (11).…”
Section: Discussionmentioning
confidence: 70%
“…Two cases had severe mucous membrane involvement and were refractory to treatments (9, 10), while another case had only ocular lesion (11).…”
Section: Discussionmentioning
confidence: 98%
“…2005). In contrary to generalized MMP, patients with typical ocular MMP rarely develop autoantibodies to laminin 5 (Coronella et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The a3 subunit of epilegrin is considered the main target antigen in epilegrin-associated MMP-like disease (Fujimoto et al 1990;Kirtschig et al 1995Kirtschig et al , 1998Dainichi et al 2005). In contrary to generalized MMP, patients with typical ocular MMP rarely develop autoantibodies to laminin 5 (Coronella et al 2005). This clinical observation may be explained by the virtual absence of b3 and c2 subchains of laminin in the normal conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
“…Coronella et al [23] describe the first reported case of pure OCP with circulating antibodies to the b3 chain of laminin 5 (detected by immunoblot and immunoprecipitation analysis) but no other recognized MMP autoantibodies. This patient was unusual in that there was ocular surface inflammation but no clinical evidence of conjunctival scarring.…”
Section: Aetiopathogenesismentioning
confidence: 97%